Virtualisasi Server Menggunakan Proxmox Untuk Mengoptimalkan Resource Server Pada SMK Bhakti Persada - Ricky Chandra; Anwar Tonggo Sitorus (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The server is a media that has an important role to provide internet access services for its users. So that the network can be used optimally, a server is needed. This study aims to design server virtualization in the Vocational School Bhakti Persada with the aim of building a flexible server infrastructure that optimizes the use of server resources, so it can be adjusted to the workload so that hardware resources are optimal. This research conducted a solution using the concept of virtualization, namely the use of proxmox to design a virtual server that can minimize maintenance costs as well as in hardware procurement. The use of hardware resources provided by the server machine has not been used optimally so that the right steps are needed to overcome this problem. Research results obtained from server virtualization using proxmox to optimize server resources can manage servers efficiently in terms of time and cost.